IMPACT OF INFLATION TARGETING MONETARY POLICY ON GDP IN ASIAN ECONOMIES (International Journal of Food and Nutritional Sciences, 2022)
Inflation targeting is one of the major goals of Central Banks across the globe. Taming inflation bolsters growth, reinforces faith of businesses and citizens in the economy, creates a vibrant business environment and enhances the ability of an economy to respond to external shocks. Inflation targeting regime is increasingly being adopted by economies all over the world on account of these reasons. Although the mode of implementation differs, major task of the Central Governments is to specify a point or range target for inflation, design the monetary policy to achieve the specified target and take accountability for it. This paper provides an empirical assessment of the effects inflation targeting monetary policy on the GDP growth in selected South East Asian economies (Thailand, Philippines and Indonesia). The paper attempts to study the relationship between the prevailing inflation (Consumer Price Index) and the resulting GDP growth in these economies. The paper provides evidence that correlation exists between inflation targeting economies and GDP growth